Internationalizing higher education: a study about barriers and possibilities - Maranhão, Carolina Machado Saraiva de Albuquerque (2017)
The importance of the internationalization of higher education is already established in the globalized society. International treaties between countries, international economic agreements and the fall of cultural barriers are some of the expressions of the strong impact of education as a sphere of multicentric formation. In Brazil, many educational institutions have adopted internationalization practices as options for their students. However, despite its importance and all efforts made regarding the internationalization of higher education, what we see in the daily life of many schools is the low level of knowledge of students about the possibilities of international mobility. In the face of this situation, and seeking to find alternatives to overcome this problem, we propose a study addressing the familiarity with this subject as expressed by the Business Administration undergraduates of a Brazilian federal higher education institutions. The data collected point to the initial hypothesis, namely, that the theme of the internationalization of higher education is widely disseminated, but the its effectiveness is understood as much more complex than it really is.